2014
DOI: 10.2175/106143014x14062131177953
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Micro‐Nano Bubbles and Potential Application in Groundwater Bioremediation

Abstract: Content of oxygen in water is a critical factor in increasing bioremediation efficiency for contaminated groundwater. Micro-nano bubbles (MNBs) injection seems to be an effective technique for increasing oxygen in water compared with traditional air sparging technology with macrobubbles. Micro-nano bubbles have larger interfacial area, higher inner pressure and density, and lower rising velocity in water, superior to that of macrobubbles. In this paper, MNBs with diameters ranging from 500 nm to 100 lm are inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(61 citation statements)
references
References 38 publications
4
56
1
Order By: Relevance
“…Microbubbles have larger interfacial area, longer life time, and higher concentration. All these features increase the degree of contact between the injected air and the contaminated soil, and thus enhance oxygen transfer efficiency in groundwater bioremediation [Li et al, 2014b;Tsai et al, 2007]. Our scaling solutions for the bubble plume development will help to estimate the residence time of bubbles in porous media.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Microbubbles have larger interfacial area, longer life time, and higher concentration. All these features increase the degree of contact between the injected air and the contaminated soil, and thus enhance oxygen transfer efficiency in groundwater bioremediation [Li et al, 2014b;Tsai et al, 2007]. Our scaling solutions for the bubble plume development will help to estimate the residence time of bubbles in porous media.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, injection of microbubbles increases the degree of contact between the injected bubbles and the contaminated soil. All these features enhance efficiency in groundwater bioremediation by promoting aerobic conditions for bioreactions and contaminant sorption [Li et al, 2014b;Tsai et al, 2007]. Furthermore, buoyant rise of the microbubbles may allow them to effectively access regions of (a) Snapshot of laboratory setup; (b) a typical bubble plume developed before the breakthrough (transient state, t < t*), the plume width (W top ) at the flume top was illustrated in yellow line; (c) calculated REV-averaged gas volume fraction distribution based on the bubble plume image shown in Figure 2b, with the solid black line showing the defined edge of the bubble plume.…”
Section: Air Spargingmentioning
confidence: 99%
“…It is nearly three times larger than air micro-nano bubbles, and the dissolved oxygen enhances durability for the longest, 16 times longer than air micro-nano bubbles. Li [7] et al found that when the particle size of the bubble is between 500 nm and 100 μm, the dissolved oxygen increases faster and the dissolved oxygen peak is higher. Adding surfactant in water can reduce the bubble size, reduce the oxygen transfer efficiency, and prolong the bubble stagnation time, increase bubble interface charge.…”
Section: Micro-nano Bubble Treatment Of Groundwatermentioning
confidence: 99%
“…Negatively charged ions (such as OH − ) in water are prone to be adsorbed on the surface of MBs, so MBs carry some negative charges [6,7]. As the bubble diameter reaches micrometers or even nanometers, the surface tension of the gas-liquid interface compresses the bubbles, thus increasing the specific surface area of bubbles and the oxygen transfer efficiency between gas and liquid [8]. The diameter of MBs is small and the bubble pressure is high.…”
Section: Introductionmentioning
confidence: 99%